2013
DOI: 10.1007/s10815-013-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc oxide nanoparticles on mouse spermatogenesis

Abstract: Objective To evaluate the effects of zinc oxide nanoparticles on mouse spermatogenesis. Methods Thirty two adult male NMRI mice were used. Experimental Groups (ZNP-1-ZNP-3) received one of the following treatments daily for 35 days: 5, 50 and 300 mg/kg zinc oxide nanoparticles respectively. Control group received only distilled water. Epididymal sperm parameters, testicular histopathology, morphometric analysis and spermatogenesis assessments were performed for evaluation of the zinc oxide nanoparticles effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 38 publications
9
86
0
1
Order By: Relevance
“…Gromadzka-Ostrowska et al showed that even small amounts of silver nanoparticles (NPs) have a toxic impact on the germ cells and reduced sperm quality [30]. Moreover, Talebi et al showed a significant decrease in epididymal sperm number, motility, and percentage of normal and live sperms in 50 and 300 mg/kg ZnONPs-supplemented mice [4]. Several studies showed the ability of different kinds of NPs to pass through the blood-testis barrier and exert their toxic action on spermatogenesis [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Gromadzka-Ostrowska et al showed that even small amounts of silver nanoparticles (NPs) have a toxic impact on the germ cells and reduced sperm quality [30]. Moreover, Talebi et al showed a significant decrease in epididymal sperm number, motility, and percentage of normal and live sperms in 50 and 300 mg/kg ZnONPs-supplemented mice [4]. Several studies showed the ability of different kinds of NPs to pass through the blood-testis barrier and exert their toxic action on spermatogenesis [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The sperm suspension from right testes was diluted 1:1 in 10 % buffered formalin. Spermatozoa were counted using improved Neubauer haemocytometer [30][31][32][33][34]. Three observers, blinded to the control and experimental groups, analyzed the sperm parameters independently.…”
Section: Grade D (Immotile) Sperms Do Not Move At Allmentioning
confidence: 99%
“…[23][24][25] Concerning the effect of ZnO NP on male reproduction, it has been reported that these NPs can act as a testicular toxicant. [26][27][28] Ji et al have reported that LCs exposed to 10/20 μM of cadmium (Cd) had reduced levels of steroid hormone due to inhibition of activation of cyclic adenosine monophosphate/protein kinase A, protein kinase C signaling pathway, and the steroidogenic enzymes StAR, CYP11A1, and 3β-HSD. 26 Also, Talebi et al reported that epithelial vacuolization, sloughing of germ cells, and detachment of mice were significantly increased after treatment with ZnO NPs, and also, ZnO NPs caused a significant decrease in seminiferous tubule diameter, seminiferous epithelium height, and maturation arrest.…”
Section: Introductionmentioning
confidence: 99%
“…26 Also, Talebi et al reported that epithelial vacuolization, sloughing of germ cells, and detachment of mice were significantly increased after treatment with ZnO NPs, and also, ZnO NPs caused a significant decrease in seminiferous tubule diameter, seminiferous epithelium height, and maturation arrest. 28 But the cytotoxic mechanism of ZnO NPs in LCs and SCs are still poorly known. Due to the lack of information regarding the reproductive toxicity of ZnO NPs, the present study was designed to investigate the possible cytotoxic effects of ZnO NPs on testicular LCs and SCs.…”
Section: Introductionmentioning
confidence: 99%